2014
DOI: 10.1063/1.4871728
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of bubble dispersion in turbulent Taylor-Couette flow

Abstract: We investigate bubble dispersion in turbulent Taylor-Couette flow. The aim of this study is to describe the main mechanisms yielding preferential bubble accumulation in near-wall structures of the flow. We first proceed to direct numerical simulation of Taylor-Couette flows for three different geometrical configurations (three radius ratios η = R 1 /R 2 : η = 0.5, η = 0.72, and η = 0.91 with the outer cylinder at rest) and Reynolds numbers corresponding to turbulent regime ranging from 3000 to 8000. The statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 50 publications
(101 reference statements)
3
64
1
Order By: Relevance
“…The left block of data are experiments and numerical simulations for microbubble drag reduction from refs. [214,215,222,223], and the right block of data are our large Re experiments with deformable bubbles [196,205,206].…”
Section: Effective Bubble Force Models Dispersed Bubbly Flow Anmentioning
confidence: 99%
“…The left block of data are experiments and numerical simulations for microbubble drag reduction from refs. [214,215,222,223], and the right block of data are our large Re experiments with deformable bubbles [196,205,206].…”
Section: Effective Bubble Force Models Dispersed Bubbly Flow Anmentioning
confidence: 99%
“…For example, if two immiscible liquids are fed continuously to a horizontally oriented Taylor vortex flow cell, a variety of spatial and spatiotemporal hydrodynamic structures arise [35][36][37][38]. More recently it has been reported that the introduction of even a small amount of gas into a vertically oriented Taylor vortex flow cell results in dramatic drag reduction on the rotating inner cylinder and nontrivial gas bubble spatial distribution [39][40][41][42]. Some recent studies have been performed in order to characterize these gas-liquid interactions in Taylor-Couette flows [43][44][45][46].…”
Section: Introductionmentioning
confidence: 98%
“…The code is based on a finite volume method, and the velocity and pressure (u,P ) are discretized on a staggered nonuniform cylindrical grid. The numerical code has been already used in laminar and turbulent configurations (see details in[33])). The spatial derivatives are computed with second order accuracy, and temporal integration is achieved by a third order Runge-Kutta scheme and a semi-implicit Crank-Nicolson scheme for the viscous terms.…”
mentioning
confidence: 99%